2006
DOI: 10.1103/physreve.73.036212
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and universality in transition to synchronous chaos with local-global interactions

Abstract: We study the coupled-map lattice model with both local and global couplings. We find necessary conditions for observing synchronous chaos and investigate the transition to synchronization as a dynamic phase transition. We discover that this transition, if continuous, shows scaling and universal behavior with the dynamic exponent z = 2. We also define and illustrate an interesting quantity similar to persistence at critical point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Usually the Lyapunov approach was able to locate γ c within a precision of 1 − 2 × 10 −4 or even better. In the present case, to simplify the analysis we keep the parameter q = 4 and we analyze system sizes ranging from L = 2 19 to L = 2 23 . The results for the exponents θ and β are shown in Fig.…”
Section: B Continuous Mapsmentioning
confidence: 99%
“…Usually the Lyapunov approach was able to locate γ c within a precision of 1 − 2 × 10 −4 or even better. In the present case, to simplify the analysis we keep the parameter q = 4 and we analyze system sizes ranging from L = 2 19 to L = 2 23 . The results for the exponents θ and β are shown in Fig.…”
Section: B Continuous Mapsmentioning
confidence: 99%
“…Gade and Hu generalized this definition and defined majority persistence for transition to chaotic synchronization in coupled maps with local-global couplings [16]. Similarly, there is a need to generalize this definition for the logistic map.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been found that critical behaviors of Ising-type spin models 2) and lattice hard-core particle models 3) can be understood from percolation transitions of properly defined clusters of the systems as in the case of random percolation models, 4) that many percolation models 5) or the Ising model 6) on different lattices has universal finitesize scaling functions, 7) and that transitions to synchronous chaos of the coupled-map lattice model 8) with both local and global couplings have nice universal and scaling behaviors. 9) We have used molecular dynamics (MD) simulations to study relaxation processes in various systems of polymer chains and Lennard-Jones (L-J) molecules; two neighboring monomers along a polymer chain are connected by a rigid bond 10) or a spring of strength k spring . 11) We find that the velocity distributions of monomers in a wide range of simulation time can be well described by Tsallis q-statistics 14), 15) and a single scaling function, where q ≥ 1 and q-statistics becomes the Maxwell-Boltzmann distribution when q → 1.…”
Section: §1 Introductionmentioning
confidence: 99%